2021
DOI: 10.3390/brainsci11070855
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Studies of Cognitive Reappraisal Success and Failure in aMCI

Abstract: Background: Although successful reappraisal relies on cognitive resources, how cognitive impairment affects brain processes related to cognitive reappraisal is not yet clear. Methods: Forty-four amnestic mild cognitive impairment (aMCI) subjects and 72 healthy elderly controls (HECs) were divided into the MCI-Failure (n = 23), MCI-Success (n = 21), HEC-Failure (n = 26), and HEC-Success (n = 46) groups according to changes in self-reported affect using reappraisal. All participants viewed 30 negative and 30 neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…Our previous study found that, compared with MCI-failure group, the MCI-Success group demonstrated larger theta power to negative images. However, the healthy elderly controls success group demonstrated stronger theta power to images preceded by more neutral descriptions compared with the healthy elderly controls -failure group (Xiao et al, 2021). While subjects in major depression performing emotionrelated tasks show decreased frontal cortex gamma power (Lee et al, 2010;Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Our previous study found that, compared with MCI-failure group, the MCI-Success group demonstrated larger theta power to negative images. However, the healthy elderly controls success group demonstrated stronger theta power to images preceded by more neutral descriptions compared with the healthy elderly controls -failure group (Xiao et al, 2021). While subjects in major depression performing emotionrelated tasks show decreased frontal cortex gamma power (Lee et al, 2010;Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 83%
“…We used a one-way ANOVA to compare LPP amplitudes in MCI, and MCI combined depressive symptom groups in response to different types of emotional stimuli (negative, neutral, and reappraisal). In five windows after stimulus onset, 400-1,000 ms (early window), 1,000-2,000 ms (middle window), 2,000-3,000 ms (late window), 3,000-4,000 ms (late window), 4,000-5,000 ms (late window), for each window, LPP was quantified as the in-window moderate activity (Xiao et al, 2021;Ding et al, 2022). The ERP analysis was conducted using ERPLAB toolbox as well as related MATLAB code.…”
Section: Event-related Potential Analysismentioning
confidence: 99%
“…Forty-three of them were diagnosed as amnestic mild cognitive impaired (aMCI group), while 51 showed no sign of cognitive impairment. All participants underwent a comprehensive Neuropsychological Test Battery (NTB) that included the Mini-Mental State Examination (MMSE), the Clinical Dementia Rating scale (CDR), and tests that evaluate the memory function, language function, executive function, and spatial visual navigation function ( Xiao et al, 2021 ; see Supplementary Materials for more details). The neuro-psychological indices of participants are given in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…It is also hypothesized that functional network changes in aMCI may be revealed following emotion regulation. Considering the relationship between cognition and cognitive reappraisal ( Xiao et al, 2021 ), one of the most effective emotion regulation strategies, cognitive reappraisal was chosen in this study. To this end, DWPLI, a method that is insensitive to volume conduction, was applied between all channels of interest for EEG signals in different bands.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the late positive potential (LPP) response to emotional stimuli is larger than that to neutral ones ( Hajcak and Olvet, 2008 ; Hajcak et al, 2010 ; Hartigan and Richards, 2017 ), and the LPP appears to be sensitive primarily to arousal level rather than valence ( Hajcak and Foti, 2020 ). Because of its sustained duration and its sensitivity to the affective properties of pictorial stimuli, the LPP is particularly well-suited to be a good candidate for studies exploring the electrophysiological correlates of emotion regulation by means of cognitive reappraisal manipulation and has featured most prominently in this work ( Krompinger et al, 2008 ; Cao et al, 2020 ; Xiao et al, 2021 ; MacNamara et al, 2022 ). Specifically, there is evidence showed that cognitive reappraisal strategy could effectively reduce the LPP and subjective ratings of unpleasantness and arousal elicited by negative pictures ( Moser et al, 2006 ; Foti and Hajcak, 2008 ; Dennis and Hajcak, 2009 ).…”
Section: Introductionmentioning
confidence: 99%